Monitoring glycolytic dynamics in single cells using a fluorescent biosensor for fructose 1,6-bisphosphate - Koberstein, JN; Stewart, ML; Smith, CB; Tarasov, AI; Ashcroft, FM; Stork, PJS; Goodman, RH (National Academy of Sciences, 2022)
Cellular metabolism is regulated over space and time to ensure that energy production is efficiently matched with consumption. Fluorescent biosensors are useful tools for studying metabolism as they enable real-time detection of metabolite abundance with single-cell resolution. For monitoring glycolysis, the intermediate fructose 1,6-bisphosphate (FBP) is a particularly informative signal as its concentration is strongly correlated with flux through the whole pathway. Using GFP insertion into the ligand-binding domain of the Bacillus subtilis transcriptional regulator CggR, we developed a fluorescent biosensor for FBP termed HYlight. We demonstrate that HYlight can reliably report the real-time dynamics of glycolysis in living cells and tissues, driven by various metabolic or pharmacological perturbations, alone or in combination with other physiologically relevant signals. Using this sensor, we uncovered previously unknown aspects of β-cell glycolytic heterogeneity and dynamics.